Development of IoT-based black soldier fly egg incubation system - Suwannayod, Suttida; Setthaya, Phattawin; Harnpornchai, Napat (Edelweiss Applied Science and Technology, 2026)
This article presents the development of an Internet of Things (IoT)-connected smart Black Soldier Fly (BSF) egg incubator designed to increase hatching efficiency and reduce manual labor. The system automates the control of temperature, humidity, and air circulation, crucial factors influencing hatching rates and larval growth. By leveraging IoT technology, the system enables remote monitoring and control of environmental conditions through a digital platform, thus minimizing errors from manual adjustments and enhancing production efficiency. The results indicate that the IoT egg incubator can achieve a high hatching rate of up to 99% under optimal conditions (temperature: 25–29°C, relative humidity: 51–70%), while also reducing incubation time compared to hatching at ambient temperature. Additionally, the system monitors resource and energy consumption by automatically adjusting environmental conditions, thereby supporting sustainable agricultural practices. In summary, this newly developed IoT egg incubator is an effective tool for BSF breeding, with the potential to transform BSF agriculture by increasing production efficiency, lowering costs, and promoting sustainability. This technology is particularly suitable for small and medium-sized farms, enabling farmers to scale up BSF production to meet the growing demand for alternative protein sources.